The Effect of Non-Surgical Periodontal Therapy on Pentraxin-3 Concentration in Gingival Crevicular Fluid of Chronic Periodontitis Patients: A Clinical Trial - Asieh Mozaffari; Mahtab Samieifar; Bahare Abd Nikfarjam; Monirsadat Mirzadeh; Shadi Assareh; Samira Mohammad Mirzapour (Shiraz University of Medical Sciences, 2022)
Statement of the Problem: Periodontitis is a multifactorial disease caused by periopathogens and its severity is determined by the host immune response. Gingival crevicular fluid (GCF) can be used for non-invasive testing to assess the host response in periodontal treatment. Pentraxins are the classic mediators of inflammation and pentraxin-3 can be used as a marker to assess response to therapy, which was investigated in this study.Purpose: This study aimed to assess the effect of non-surgical periodontal therapy on GCF level of pentraxin-3 in patients with chronic periodontitis.Materials and Method: 25 patients with chronic periodontitis (CP) and 25 periodontally healthy controls were evaluated. Pocket probing depth, clinical attachment loss, plaque index, gingival index, and bleeding on probing were measured in both groups. GCF samples were collected using paper strips to assess the level of pentraxin-3. In the CP group, GCF samples were collected from the highest clinical attachment loss, pocket probing depth, and bone loss at baseline and six weeks after non-surgical therapy. The level of pentraxin-3 in the GCF was quantified by enzyme-linked immunosorbent assay (ELISA). Data were analyzed using SPSS version 23.Results: Pentraxin-3 in GCF of CP patients before treatment (6.72±4.63 ng/mL) was higher than the control group (4.43±2.85 ng/mL). Pentraxin-3 in patients after non-surgical therapy (3.2±2.66 ng/mL) decreased significantly compared to the baseline (p= 0.04) and its level after treatment was not significantly different from the control group (p= 0.14).Conclusion: Pentraxin-3 in GCF of CP patients was higher than healthy controls and decreased in response to non-surgical periodontal therapy. Thus, it can be used as an inflammatory marker for detection of patients at risk of CP. However, further studies with larger samples and longer follow-ups in different populations are required to confirm our findings.